The plot-composition organization of dramatic works of Ukrainian emigration writers in the middle of the twentieth century - Антонович, Світлана (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article is devoted to the study of plot-composition organization of dramatic works of Ukrainian emigrants-writers in the middle of the twentieth century. It has been found out that the features of the plays’ structure are mostly experimental by nature, including the wide involvement of such components as the prologue, the epilogue, the interlude inserts and so on to the drama. The compositional possibilities of the works are outlined in L. Pirandello’s scheme “play-in-the-play”, which expresses the specificity of the epoch, demonstrates its disorder, as well as facilitates searches in both content and form. Reception of the framing, in violation of the logic of the portrayed events, reveals the relationship between the theater and the viewer (plays by I. Kostetskyi, I. Cholhan, A. Yuryniak and others are illustrative). It is emphasized that the introduction of the “master of ceremonies” (Prologue as an actor) in the text of the drama is intended to explain its plot-shaped paradigm, the accumulation of organizational components, which helps an adequate reception of the portrayed (mostly I. Cholhan’s comedies). In such dramatic compositional parts as the prologue, the epilogue, the interludes the writers focus readers’ attention on topical issues of conceptual importance for understanding the epoch. The idea of a transformed prologue, more rarely an epilogue, is significant in emigration dramaturgy, because it declared as the sphere of the “presence” of the author, expresses the desire of the individual (the emigrant artist) to comprehend and express the understanding of the character. The interlude inserts broaden the concept of the work: they serve as an emotional accompaniment to the main events, focus the recipient on the ideological and philosophical essence of the play, combine structural parts of the text, activate the analytical readers’ perception of the work. It is proved that the search character of the analyzed plays is an indispensable feature of the dramatic acquisition of Ukrainian emigrants-writers of the middle of the twentieth century.